2019
DOI: 10.1093/ofid/ofz525
|View full text |Cite
|
Sign up to set email alerts
|

Differential Composition of Vaginal Microbiome, but Not of Seminal Microbiome, Is Associated With Successful Intrauterine Insemination in Couples With Idiopathic Infertility: A Prospective Observational Study

Abstract: Background Vaginal and seminal microbiomes have gained increasing interest for their involvement in reproductive health and fertility. However, their role in reproductive outcome is not fully understood yet. In this study, we aimed to correlate the vaginal and the seminal microbiome of 23 couples with idiopathic infertility to the clinical pregnancy rate after intrauterine insemination (IUI). Methods Vaginal swabs and seminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 37 publications
3
59
1
1
Order By: Relevance
“…Interestingly, they found that the prevalence of Gardnerella vaginalis in the vaginal microbiome was higher in women whose partners had leukocytospermia; in addition, they also highlighted a reduction of Lactobacillus crispatus and a high concordance between semen and vaginal microbiome, after sexual intercourse [ 99 ]. Subsequently, Amato et al analyzed the vaginal and seminal microbiome of 23 couples with idiopathic infertility with the aim to correlate microbial features with the pregnancy rate after intrauterine insemination [ 100 ]. They found that the vaginal microbiome of idiopathic infertile women differed from controls, whereas the semen not; in addition, they found, among the vaginal microbiome of idiopathic infertile women different patterns of Lactobacillus species, Lactobacillus crispatus being associated to the higher rate of intrauterine insemination success [ 96 ].…”
Section: Female Reproductive System Microbiome and Infertilitymentioning
confidence: 99%
“…Interestingly, they found that the prevalence of Gardnerella vaginalis in the vaginal microbiome was higher in women whose partners had leukocytospermia; in addition, they also highlighted a reduction of Lactobacillus crispatus and a high concordance between semen and vaginal microbiome, after sexual intercourse [ 99 ]. Subsequently, Amato et al analyzed the vaginal and seminal microbiome of 23 couples with idiopathic infertility with the aim to correlate microbial features with the pregnancy rate after intrauterine insemination [ 100 ]. They found that the vaginal microbiome of idiopathic infertile women differed from controls, whereas the semen not; in addition, they found, among the vaginal microbiome of idiopathic infertile women different patterns of Lactobacillus species, Lactobacillus crispatus being associated to the higher rate of intrauterine insemination success [ 96 ].…”
Section: Female Reproductive System Microbiome and Infertilitymentioning
confidence: 99%
“…In respect of the vagina, Campisciano et al found that infertile patients (especially those with idiopathic infertility) had higher richness and diversity of species than healthy controls (Chao1: Control – 419, Idiopathic – 579 - p<,05; Simpson’s index: Control - 1,5, Idiopathic – 2,4, Infertile – 2,6 – p<,05) ( 40 ). In contrast, Amato et al found no statistically significant differences in diversity between infertile patients and controls ( 41 ). Likewise, Kitaya et al found no differences in diversity between patients with history of RIF showed compared to other infertile patients ( 35 ).…”
Section: Resultsmentioning
confidence: 89%
“…flora in disfavour of L. iners and L. crispatus that may be a cause for some of the idiopathic infertility, rather than isolated bacteria dominance ( 40 ). Amato et al found a similar trend but with no statistical significance, maybe due to the small size of the sample ( 41 ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations